The law on minimum wages in Malaysia - Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2013)
The International Labour Conference had, in its 54th session on 22 June 1970, adopted the Minimum Wage Fixing Convention, 1970 (No. 131) and the Minimum Wage Fixing Recommendation 1970 (No. 135), which requires the ratifying states to establish a minimum wage fixing machinery which in turn, is capable of determining and periodically reviewing and adjusting minimum wage rates. Its primary purpose is to aid the underpaid; the nation’s working population and those who lack sufficient bargaining power to secure for themselves a minimum subsistence wage. Having said the above, this chapter discusses the minimum wage payment with reference to ILO’s instruments, the practice in Malaysia with reference to the Minimum Wages Order 2012 and the approach from the Islamic perspective.